Ru(EDTA) mediated partial reduction of O2 by H2S. Issue 16 (26th March 2015) - Chatterjee, Debabrata; Jaiswal, Namita; Sarkar, Papiya
Abstract : [Ru III (EDTA)(pz)] − (EDTA 4− = ethylenediaminetetraacetate), pz = pyrazine) mediates two-electron reduction of O2 to produce H2 O2 using H2 S as a reducing agent. Abstract : An effective procedure for selective reduction of O2 to H2 O2 exploring the use of hydrogen sulfide, an obnoxious industrial pollutant as reductant is reported herein. The reduction of [Ru III (EDTA)pz] − (EDTA 4− = ethylenediaminetetraacetate; pz = pyrazine) by hydrogen sulfide resulting in the formation of a red [Ru II (EDTA)pz] 2− complex ( λ max = 462 nm) has been studied spectrophotometrically and kinetically using both rapid scan and stopped-flow techniques. The time course of the reaction was followed as a function of [HS − ]i, pH (5.5–8.5), and temperature. Alkali metal ions were found to have a positive influence (K + > Na + > Li + ) on the reaction rate. Kinetic data and activation parameters are interpreted in terms of a mechanism (admittedly speculative) involving outer-sphere electron transfer between the reaction partners. Reaction of the red [Ru II (EDTA)pz] 2− complex with molecular oxygen regenerates the [Ru III (EDTA)pz] − species in the reacting system along with the formation of H2 O2, a partially reduced product of dioxygen (O2 ) reduction. A detailed reaction mechanism in agreement with the spectral and kinetic data is presented.